Erratum to: On the Detection of Exploitation of Vulnerabilities That Leads to the Execution of a Malicious Code - Kosolapov, Y. V. (Automatic control and computer sciences, 2022)
An Erratum to this paper has been published: https://doi.org/10.3103/S0146411622070094